"Parents, Me & X-Sports": Mapping the BMX Culture in Contemporary China. (October 2019) - Ding, Yiyin
Since the debut of BMX (bike motocross) cycling in the Beijing Olympics, lifestyle sports have gradually entered the public limelight and gained popularity in China. Lifestyle sports that celebrate leisure, excitement, and individuality have steadily grown a crowd of youth followers in major Chinese cities. This article contextualizes the BMX culture in contemporary China, particularly the local cultural dynamics of the subculture. Using evidence gleaned from interviews and media representations, I argue that while many of the features of development of BMX culture in China mirror that in the West acceptance by the family has become a central theme when it comes to BMX riders' career choice in China—a "Parents, Me & X-sports" relationship.